Characterization in respect to degradation of titanium‐coated polypropylene surgical mesh explanted from humans - Farr, Nicholas T. H.; Klosterhalfen, Bernd; Noé, Günter K. (Journal of biomedical materials research. Part B, Applied biomaterials, 2023)
Titanium‐coated polypropylene (Ti‐PP) mesh was introduced in 2002 as a surgical mesh for the treatment of hernias and shortly after for pelvic floor surgery, with the aim of improving biocompatibility when compared to non‐titanised/regular PP mesh implants. The application of a titanium coating could also be beneficial to address concerns regarding the exposure of PP in an in vivo environment. Many studies have shown that PP, although it is widely accepted as a stable polymer, is subject to oxidation and degradation, such degradation affects the mechanical behavior, that is, the stiffness and tensile strength of PP mesh. Despite the wide clinical use of Ti‐PP surgical meshes, no study has yet investigated the residual material properties post clinical deployment and subsequent explantation. In this study, two explanted Ti‐PP mesh samples each having different incorporation durations from two patients were examined. Material analysis conducted within this study includes the following techniques: attenuated total reflectance‐Fourier transform infrared spectroscopy (ATR‐FTIR), Raman spectroscopy, low voltage – scanning electron microscopy (LV‐SEM), backscattered electron (BSE) imaging, energy dispersive X‐ray spectroscopy (EDS) and secondary election hyperspectral imaging (SEHI). The hypothesis of this study is that the Ti coating successfully shields the PP mesh from oxidative stress in vivo and thus protects it from degradation. The results of this analysis show for the first time evidence of bulk oxidation, surface degradation, and environmental stress cracking on explanted Ti‐PP meshes.